2021
DOI: 10.1177/00380261211049024
|View full text |Cite
|
Sign up to set email alerts
|

Joining up well-being and sexual misconduct data and policy in HE: ‘To stand in the gap’ as a feminist approach

Abstract: This article joins up evidence and policy relating to two linked concerns in higher education (HE) that are treated as unrelated: postgraduate research student (PGR) well-being, and staff sexual misconduct towards students. Against the standard methodology of systematic reviews, we build on feminist approaches to apply a ‘re-performance’ approach to the review. Re-performance re-enacts established methods, contextualising previous analysis through ethnographic and desk-based research, exposing gaps in evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We understand lad culture to be facilitated by a masculinised, neoliberal framework embedded within institutions and perpetuated by people in positions of power (see Phipps and Young 2015). Concerns have been raised, for example, about sexual misconduct perpetrated by staff against students and the ways in which institutions often fail to address misconduct (see, for example, Oman and Bull 2021). Lad culture enacted and experienced by students cannot be understood in isolation from the role of universities in tolerating and bolstering lad culture, or from societal issues surrounding masculinity and gender-based violence.…”
Section: Theorising Masculinity and Campus Lad Culturementioning
confidence: 99%
“…We understand lad culture to be facilitated by a masculinised, neoliberal framework embedded within institutions and perpetuated by people in positions of power (see Phipps and Young 2015). Concerns have been raised, for example, about sexual misconduct perpetrated by staff against students and the ways in which institutions often fail to address misconduct (see, for example, Oman and Bull 2021). Lad culture enacted and experienced by students cannot be understood in isolation from the role of universities in tolerating and bolstering lad culture, or from societal issues surrounding masculinity and gender-based violence.…”
Section: Theorising Masculinity and Campus Lad Culturementioning
confidence: 99%
“…In a Likert scale analysis done among undergraduate students in India shows that 82.4% of the students had average understanding about sexual harassment, 13.2% had strong knowledge, and 4.4% had poor knowledge regarding sexual harassment [16]. A study in a different setup found that, evidence regarding sexual misbehavior by staff members and student well-being is dispersed over several academic fields, including psychology, law, sociology, education, organization and management studies, health sciences, and policy studies [17].…”
Section: Discussionmentioning
confidence: 99%
“…Other core problems that tend to disappear from view in the UK include: reduced student access to counselling services, insufficient support of students with severe and ongoing mental health problems, levels of precarity amongst university staff and their potential impact on both staff and student mental health, and the mental health and wellbeing of university staff (Morrish, 2019;Erickson et al, 2020). Additionally, many aspects of university lifesuch as the effects of sexual misconductremain inadequately researched for their potential contribution to mental ill health (Oman & Bull, 2021). A rapid review investigating the relationship between financial stress and student mental health in the UK concluded that while financial stress might be associated with mental health outcomes, most studies were small in size and limited in design (McCloud & Bann, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, which we consider here as an exemplary site, these infrastructures rely extensively on digitalisation and the involvement of corporate actors, which bring multiple political and ethical implications. However, literature and data on student mental health and well-being rarely address the systems and infrastructures used in higher education (HE) (Kotouza et al, 2021), and the fragmentation of evidence used obscures potential causes of ill health (Hern andez-Torrano et al, 2020;Oman & Bull, 2021). Social theorists have addressed how the political-economic configurations of late capitalism have damaging psychosocial effects, at the same time as they magnify focus on producing and measuring subjects' 'wellbeing' (Davies, 2011).…”
Section: Introductionmentioning
confidence: 99%